Empagliflozin Superior to Glimepiride as Second-line Treatment in T2DM - Parry, Nicola (MD Conference Express, 2014)
Empagliflozin is superior to glimepiride as an add-on treatment option for patients with type 2 diabetes mellitus who have not achieved good glycemic control on metformin, according to results from the Efficacy and Safety of Empagliflozin (BI 10773) With Metformin in Patients With Type 2 Diabetes trial that are presented in this article.